Thoughts on AI Interoperability. - Cerf, Vinton G. (Communications of the ACM, 2024)
The author reflects on the interoperability of machine learning (ML) and large language model (LLM) systems, considering the potential for specialized APIs, federated learning, and cooperative interaction among ML systems, suggesting the need for semantic and syntactic exchange standards to ensure precision in information exchange. They invite input from more qualified individuals to further develop these ideas.